(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
جرى تقويم ثمانية مدخلات من أصناف القمح القاسي T. Durum تحت ظروف المنطقة الساحلية بالقرب من مدينة طرطوس خلال موسمي الزراعة (2000-2001 و2001 –2002), المدخلات هي: Kidur, Jaguor, Latino,-M-67, Waha s, D-771,Verio, Qadruro. أعطيت الأرقام بالتسلسل( 1, 2, 3, 4, 5 ,6, 7 ,8) واستخدم الصنف cham 1 شاهد . جمعت البيانات لثماني صفات أساسية فضلا عن خصائص الغلة, وحللت البيانات إحصائيا" بطريقة مكونات التباين التجميعي لعامي الدراسة. أظهرت النتائج وجود فروق معنوية عالية بين المدخلات من جهة وكذلك بين المدخلات والشاهد من ناحية أخرى, أفضل المدخلات (1 و2 و8) لما تميزت به من قيم مرتفعة لدليل الحصاد مصحوبة بتقديرات عالية لصفة وزن الألف حبة /غ, كذلك عدد الاشطاءات المثمرة, وارتباطاتها القوية الإيجابية عالية المعنوية مع غلة الحبوب. Eight varieties (Kidur, Jaguor, Latino, m-67, Wahas, d-771, Verio, Qadruro) series no (1,2,3,4,5,6,7,8) of introduced European durum wheat (Triticum durum) were experienced throuht two years(2000/2001- 2002/2002) at coastal region of Syria. using Vito local variets, (cham-1) as Control. The results of this studs show that, there are significance differences(at level, 1% and 5%), Among introduced varieties ,(genotypes) in one side and between local variety (control) and introduced European durum wheat on other hand side the best varieties are (1,2,8), accordionist login level of harvesting index %, associated with bus value of 1000- kernel waist muse number of yielding tiller, and strong, positive correlation with grain yield.